Utilizing Environmentally Friendly Materials as Sustainable Urban Vertical Farming Racks with Maximum Load - Rahmat Rahmat; Dean Anggara Putra; Wahyu Sutomo (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
The primary challenges in rack design are the use of weak materials and materials that are harmful to the environment. This research aims to develop an optimal rack design by evaluating the safety factors of the frame structure to ensure its reliability and safety, utilizing environmentally friendly Acrylonitrile Butadiene Styrene (ABS) material. The testing method employed is a Solidworks-based simulation, which enables a more efficient and precise design process through parametric modeling for structural optimization. The synergy between design methodology and software-based simulation, combined with the advantages of ABS material, can produce innovative, effective, and sustainable engineering strategies, potentially accelerating product development. In the proposed design, the simulation load is applied to the four frame legs. A maximum load of 50 kg is applied to each of the top three shelves, while the bottom shelf is subjected to a load of 100 kg (equivalent to 1000 N). This configuration assumes the bottom rack bears a greater load due to accommodating a larger volume of water for circulation. The analysis revealed a maximum compressive strength of 13.734 MPa at the joint end of the loaded surface, with the smallest stress value recorded at 1.149 MPa. The greatest load occurred at joint level no. 4, as this section is subjected to water pressure from the pump. Strain distribution analysis showed a maximum strain of 0.00491 at the same joint, while the minimum strain was 0.00041. The greatest load was located at joint level no. 1, where a water tank holding approximately 100 liters of water is situated. Displacement analysis of the shelf above the floor indicated a maximum deformation of 48.165 mm (categorized as light deformation) and a minimum deformation of 0 mm.